Factors Influencing Juvenile Recidivism at Narathiwat Province's Observation and Protection Center - Samah, Youreesa; Dureh, Nurin; Ma-a-lee, Arinda (Asian Health, Science and Technology Reports, 2024)
The purpose of this study was to investigate the factors that contribute to juvenile recidivism at Narathiwat Province's Observation and Protection Centre. The data used are secondary data gathered from the risks and needs assessment from the Juvenile Observation and Protection Centre of Narathiwat province, which was recorded between 2017 and 2021. There are 843 offenses committed by juveniles, and this study compares juvenile recidivism to juvenile non-recidivism. The multiple logistic regression model was applied, and the results showed that the overall proportion of juvenile recidivism is approximately 13.45%. Factors associated with juvenile recidivism include the year of the offence, the month, location, type of litigation, substance abuse history, theft history, and whether the individual has ever run away from home. The model indicates that the juvenile recidivism rate was higher than the overall proportion in 2021, especially during July, August, and September. Additionally, juveniles from rural areas, those who have ever used substances, committed theft, or run away from home are more likely to recidivism. According to the study's findings, to effectively address the issue of juvenile recidivism in Narathiwat Province, organizations and institutions in the community, families and guardians, law enforcement and related legal agencies as well as community members, should collaborate to solve the problem at various levels, focusing on each individual and receiving support from the Observation and Protection Center.